Risk factors associated with postpartum depression and PTSD after birth in a sample of Slovak women - Barbora Ďuríčeková; Zuzana Škodová; Martina Bašková (Heliyon, 2024)
Background: Pregnancy, childbirth and the postpartum period represent a unique experience in a woman's life that significantly changes their life. Methods: The aim of the study is to analyse risk factors of postpartum depression and posttraumatic stress disorder symptoms after birth in a sample of women in Slovakia. Data from the INTERSECT project were collected, including 437 postpartum women (mean age 30.5 ± 4.8). Posttraumatic stress disorder was (PTSD) measured through the City BiTS questionnaire, postpartum depression (PPD) symptoms were detected using the Edinburgh Postnatal Depression Scale (EPDS) and birth satisfaction was measured by the Birth Satisfaction Scale- Revised (BSS-R). Results: An increased risk for the development of PPD (the EPDS score >12.5) was found in 11.4 % of respondents, PTSD after birth was identified among 2.8 % of respondents. In the linear regression models, birth satisfaction (95%CI: 0,56; −0,19), subjective perception of birth (95%CI: 0,82; 1,63), previous trauma (95%CI: 0,27; 3,74), respect during birth (95%CI: 5,08; −0,45), and health complications of both mother (95%CI: 0,12; 2,81) and child (95%CI: 1,53; 1,84) were found significantly associated with the posttraumatic stress symptoms after birth (total explained variance 37 %). Subjective perception of birth as traumatic (95%CI: 0,82; 1,63), previous trauma in the anamnesis (95%CI: 0,27; 3,74) and respect during birth (95%CI: 5,08; −0,45) were significantly associated with the depression symptoms (total explained variance 15 %). Conclusion: Subjective perception of birth, birth satisfaction, previous trauma in anamnesis as well as lack of respect during birth were found as crucial risk factors for both PPD and postpartum PTSD.